The Charter and the Acts and Laws of His Majesties Colony of Rhode Island, and Providence-Plantations in America, 1719, at 86 (Sidney S. Rider, ed. 1895) - (:unkn) unknown (My University, 1718)
Provided that "all male Persons . . . from the Age of Sixteen, to the Age of Sixty Years, shall bear Arms." Arms were "one good Musket, or Fuzee, the Barrel whereof not to be less than three foot and an half in length," plus a sword or bayonet, a pound of gunpowder, thirty bullets, six flints, and a cartridge box.
Keywords: MILITIAS; DEFINITIONS